An insight into the intricacies of lingual paraphrasing pragmatic discourse on the purpose of synonyms - Jabir Al Nahian; Abu Kaisar Mohammad Masum; Muntaser Mansur Syed; Sheikh Abujar (Bulletin of Electrical Engineering and Informatics, 2022)
The term "paraphrasing" refers to the process of presenting the sense of an input text in a new way while preserving fluency. Scientific research distribution is gaining traction, allowing both rookie and experienced scientists to participate in their respective fields. As a result, there is now a massive demand for paraphrase tools that may efficiently and effectively assist scientists in modifying statements in order to avoid plagiarism. natural language processing (NLP) is very much important in the realm of the process of document paraphrasing. We analyze and discuss existing studies on paraphrasing in the English language in this paper. Finally, we develop an algorithm to paraphrase any text document or paragraphs using WordNet and natural language tool kit (NLTK) and maintain "Using Synonyms" techniques to achieve our result. For 250 paragraphs, our algorithm achieved a paraphrase accuracy of 94.8%.